A Study of the Effect of Sense of Coherence and Proactive Coping upon Health and Quality of Life: Exploring the Relationship between Sense of Coherence, Proactive Coping, and Health-related Quality of Life in Elderly Individuals (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The present study was undertaken to assess the contribution of Sense of coherence, Proactive coping to the prediction of Health and Quality of life among elderly people. A sample of 400 elements from both sexes was drawn. Mean, Sd, Pearson correlation and regression analysis was computed with the help of SPSS. Results revealed that Sense of coherence, Proactive coping don’t make significant contribution to the prediction of criterion variable i.e. health, though these results are contrary to previous findings for the same. However, Sense of coherence, Proactive coping contribute significantly to the prediction of another criterion variable i.e. Quality of life.